Analysis of the Relationship between Patient Family Knowledge about Infections in Post-Operative Wounds in Supporting the Post-Operative Patient Wound Healing Process: Study at dr. Soekardjo Regional General Hospital, Tasikmalaya, Indonesia - Sumiati, Eet (Sriwijaya Journal of Surgery, 2024)
Introduction: Post-operative wound infection is a serious complication that can hinder the healing process. The patient's family's knowledge about post-operative wound infections can play an important role in supporting the healing process. This study aims to analyze the relationship between the patient's family's knowledge about infections in post-operative wounds and the process of wound healing in post-operative patients at dr. Soekardjo Regional General Hospital Tasikmalaya. Methods: This research used a cross-sectional design with a total of 52 respondents selected by purposive sampling. Data was collected using a questionnaire to measure the patient's family's knowledge about post-operative wound infections and observation sheets to assess the wound healing process. Data analysis was carried out using the Chi-square test. Results: The majority of respondents were 32 years or older. Respondents' education was dominated by secondary level. The majority of respondents have incomes greater than or equal to the UMR. The majority of respondents had sufficient knowledge about post-operative wound infections, but there were still 17.31% of respondents who had insufficient knowledge. The results of the study showed that there was a significant relationship between the patient's family's knowledge about post-operative wound infections and the wound healing process (p-value < 0.05). Conclusion: The patient's family's knowledge about post-operative wound infections can support the patient's post-operative wound healing process.